2019
DOI: 10.1002/jobm.201900497
|View full text |Cite
|
Sign up to set email alerts
|

H‐NS, IHF, and DnaA lead to changes in nucleoid organizations, replication initiation, and cell division

Abstract: Histone-like nucleoid-structuring protein (H-NS) and integration host factor (IHF) are major nucleoid-associated proteins, and DnaA, a replication initiator, may also be related with nucleoid compaction. It has been shown that proteindependent DNA compaction is related with many aspects of bacterial physiology, including transcription, DNA replication, and site-specific recombination. However, the mechanism of bacterial physiology resulting from nucleoid compaction remains unknown. Here, we show that H-NS is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…MG1655 and subDnaA box V cells were transformed with pOZihfBA3-1, a derivative of pBAD18 carrying the IHF coding genes ihfA and ihfB , downstream of an arabinose-inducible promoter ( 7 ), and the resulting strains were analyzed for cell size and DNA content as mentioned earlier. When IHF expression was induced in the wild-type DARS2 cells at 42°C, the four-chromosome peak was moderately increased compared with cells without induction (Figure 3B , 42°C), consistent with previous data ( 57 ). However, in subDnaA box V cells grown under the same conditions, IHF overexpression dramatically stimulated replication initiation, diminishing the two-chromosome peak while increasing the four-chromosome peak.…”
Section: Resultssupporting
confidence: 92%
“…MG1655 and subDnaA box V cells were transformed with pOZihfBA3-1, a derivative of pBAD18 carrying the IHF coding genes ihfA and ihfB , downstream of an arabinose-inducible promoter ( 7 ), and the resulting strains were analyzed for cell size and DNA content as mentioned earlier. When IHF expression was induced in the wild-type DARS2 cells at 42°C, the four-chromosome peak was moderately increased compared with cells without induction (Figure 3B , 42°C), consistent with previous data ( 57 ). However, in subDnaA box V cells grown under the same conditions, IHF overexpression dramatically stimulated replication initiation, diminishing the two-chromosome peak while increasing the four-chromosome peak.…”
Section: Resultssupporting
confidence: 92%
“…Huang et al reported that histone-like proteins, H-Ns and IHF, in E. coli affected the higher-order DNA compaction while H-NS and IHF regulated the gene expression as transcription factors. Similarly, the transcription factor DnaA has also been shown to affect the compaction of nucleoid [68] , [69] and RNA structures [70] . Le Berre et al observed the link between gene expression and chromosomal spatial organization, which turned out to be essential for bacterial adaptation to changing environmental circumstances [71] .…”
Section: Perspectivesmentioning
confidence: 99%